Uniportal VATS Lobectomy and Decortication: Not an Everyday Occurrence. Issue 1 (January 2021) - Newman, Joshua S.; Renzi, Alexandra S.; Glassman, Lawrence; Lee, Paul C.; Jurado, Julissa; Hyman, Kevin; Zeltsman, David
Management of trapped lung with an underlying lung lesion and hydropneumothorax remains controversial. Furthermore, Aspergillus empyema and aspergilloma are rare pathologies for which uniportal video-assisted thoracoscopic (VATS) surgical management remains controversial. We present a young patient referred to our service after recent hospitalization for pneumonia. The patient was found to have a chronic effusion with a right lower lobe cystic parenchymal lesion and was taken to the operating room. The patient underwent right uniportal VATS surgery with evacuation of empyema, total pulmonary decortication, and right lower lobectomy. His postoperative course was unremarkable, and he was discharged home. Postoperative workup demonstrated lymphocyte variant hypereosinophilia. He continues to follow with thoracic surgery at the time of this report and remains asymptomatic. We conclude that uniportal VATS is a most minimally invasive, safe, and efficient approach for management of complex intrathoracic pathology including total pulmonary decortication and lobectomy.